The racially diverse affective expression (RADIATE) face stimulus set. (December 2018) - Conley, May I.; Dellarco, Danielle V.; Rubien-Thomas, Estee; Cohen, Alexandra O.; Cervera, Alessandra; Tottenham, Nim; Casey, BJ
Highlights: An open-access face stimulus set of 1721 racially diverse expressions is described. Sixteen different emotions in color and in black and white versions are included. Psychometric results support the validity and reliability of the face stimuli. Validity and reliability measures for each adult face stimulus are provided. Abstract: Faces are often used in psychological and neuroimaging research to assess perceptual and emotional processes. Most available stimulus sets, however, represent minimal diversity in both race and ethnicity, which may confound understanding of these processes in diverse/racially heterogeneous samples. Having a diverse stimulus set of faces and emotional expressions could mitigate these biases and may also be useful in research that specifically examines the effects of race and ethnicity on perceptual, emotional and social processes. The racially diverse affective expression (RADIATE) face stimulus set is designed to provide an open-access set of 1, 721 facial expressions of Black, White, Hispanic and Asian adult models. Moreover, the diversity of this stimulus set reflects census data showing a change in demographics in the United States from a white majority to a nonwhite majority by 2020. Psychometric results are provided describing the initial validity and reliability of the stimuli based on judgments of the emotional expressions.